Southeast Asia Scenarios Workshop - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In a workshop from 3 to 5 November in Ha Long Bay, Vietnam organized by the FAO EPIC program, CCAFS, UNEP World Conservation Monitoring Centre, NOMAFSI and MARD, regional stakeholders from development organizations, governments, private sector, civil society and academia came together to outline scenarios on future socio-economic drivers of change for food security, environments and livelihoods in Southeast Asia to be considered together with future climate change. These scenarios can be used to help develop better policies and investments. Photo: Elisabeth van de Grift.